The Effectiveness of "Alef" as the digital curricula Educational Program in the Students' Learning Recitation Rules and Their Attitudes Toward it - Aljallad, Majed Zaki; Suliman Al Arood , Mohammad Abdulsalam; Baioumy, Nashaat (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to investigate the effectiveness of "Alef" educational program in the students' learning recitation rules and their attitudes toward it. The sample consisted of (87) 8th grade students (41 male, 46 female) in UAE, who were divided into two groups: An experiment group that studied the course using "Alef" program, and control group that studied the same course using the Holley Qur'an. The instrument repressed in: Oral and writing tests in recitation rules, and attitude scale. The results showed a significant difference between the students' achievement on both oral and writing tests due to: Teaching method variable in favor of the experimental group, and gender variable in favor of females. The results also indicated high positive attitudes towards "Alef" educational program. According to these findings, the study recommended the use of "Alef" educational program in all schools with different stages and paths, especially in the future shifting towards the digital curricula.